POLITICAL POPULISM IN 2019 PRESIDENTIAL ELECTION: NARRATING ISLAMIC PARADIGM ON CULTURAL IDENTITY OF TOWANI TOLOTANG COMMUNITY - Muhammad, Firdaus; B, Jalaluddin; Khaerunnisa; Rezky Z., Muh.; Irnawati (Jurnal Adabiyah, 2022)
This article examines Towani Tolotang’s political reflections as a minority group during the 2019 Presidential Election campaign. Minority groups are frequently regarded idiosyncratically by the majority group and even the state, as evidenced by the limited narratives about them during the Presidential Election. This study is currently focused on Towani Tolotang’s political reflection as a minority group in the 2019 Presidential Election, particularly in light of the democratic constitution and Islamic teachings. This study employs a qualitative method and Edmund Husserl’s Transcendental Phenomenology approach to analyze this phenomenon through an interview with an informant from their community named Uwa Jappi Pattedungi. Gathering information from informant, categorizing information, analyzing the categorization, and drawing conclusions are some of the stages used to examine the data obtained from the interview. According to Surah An-Nahl verse 90 and An-Nisa paragraph 135, the Towani Tolotang group’s political reflection is founded on the value of their local wisdom in the form of tolerance, which turns out to be comparable with the substance of democracy, namely openness and equality, and the substance of Islamic teachings, namely justice. However, as a result of the polarization of political support, the potential for local wisdom has been reconstructed into a ’Political Populism’ movement, particularly among groups more predisposed to an exclusivist political stance. To address this issue, it is essential to change institutions and belief systems, which can be seen in political communication that emphasizes the importance of equality in majority-minority relationships. ملخّص تركز هذه الرسالة على الانعكاس السياسي لتواني تولوتانج كمجموعة أقلية في فترة حملة الانتخابات الرئاسية لعام ٢٠١٩. غالبًا ما يتم التعامل مع مجموعات الأقليات بشكل خاص من قبل مجموعة الأغلبية وحتى الدولة ، وهو ما يمكن رؤيته من خلال الروايات المحدودة عنها خلال الانتخابات الرئاسية بالأمس. في هذه النقطة ، يهدف هذا البحث إلى النظر إلى انعكاس تواني تولوتانغ السياسي كمجموعة أقلية في لحظة فترة الانتخابات الرئاسية لعام ٢٠١٩ ، خاصة من وجهة نظر الدستور الديمقراطي والتعاليم الإسلامية. تطبق هذه الدراسة نهج Edmund Husserl للظواهر المتعالية لفهم هذه الظاهرة من خلال مقابلة مع مخبر من مجتمعهم يُدعى Uwa Jappi Pattedungi. لتحليل البيانات التي تم العثور عليها من المقابلة ، تم اتخاذ عدة خطوات ، وهي جمع المعلومات من المخبرين ؛ تصنيف نتائج المعلومات ؛ تحليل التصنيف واستخلاص النتائج. تثبت نتائج هذه الدراسة أن الانعكاس السياسي لمجموعة تواني تولوتانج يستند إلى قيمة حكمتهم المحلية في شكل قيمة التسامح. - سورة النحل (٩٠) و سورة النساء (١٣٥) . ولكن ، فقد أعيد بناء إمكانية الحكمة المحلية في حركة "الشعبوية السياسية" نتيجة استقطاب الدعم السياسي ، خاصة تجاه الجماعات التي تميل أكثر إلى موقف التفرد في السياسة. لإختمام هذه المشكلة ، من الضروري إصلاح المؤسسات والعقليات التي يمكن رؤيتها من خلال التواصل السياسي الذي يركز أكثر على قيمة المساواة في العلاقة بين الأغلبية والأقلية